Stratifikasi Konflik Sosial dalam Film Inch’ Allah Karya Anaïs Barbeau-Lavallete - Salma, Inas; Nurlinah, Nurlinah; Rohanda, Rohanda (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2025)
This research analyzes the Stratification of Social Conflict in the Film Inch’ Allah by Anais Barbeau Lavallete. This research uses a qualitative paradigm with Max Weber's Sociology of Social Conflict Literature approach. The formal object in this research is Max Weber's Sociology of Literature, and the material object is Inch’ Allah Movie. The purpose of this research is to identify the form of social conflict and analyze the Stratification of Social Conflict that can provide a comprehensive framework. The results and discussion show an in-depth analysis of the form of social conflict, the structure of social conflict, and the factors that trigger social conflict. Which can be categorized in the form of differences in social interests and stratification due to the existence of power, privileges as well as social status. Inch'Allah film represents the reality of the Palestinian-Israeli conflict. the form of conflict reality that occurs in Inch'Allah film includes: tight security and inspection, searches, shooting, interrogating and threats made by the Israeli Army against the Palestinian population.